Physiological and biomechanical aspects of rifle carriage during biathlon skiing - Jonsson Kårström, M. (Mid Sweden University, Faculty of Human Sciences, Department of Health Sciences, 2023)
Biathlon is an endurance-based winter sport that combines crosscountry (XC) skiing with rifle marksmanship. While skiing, biathletes carry the rifle (weighing = 3.5 kg) on their backs. However, research regarding the effects of rifle carriage in biathlon is lacking. Therefore, the aim of this body of work was to investigate how rifle carriage in biathlon affects physiological and biomechanical variables related to biathlon skiing performance, and possible sex differences associated with rifle carriage. Physiological (Study I) and kinematical (Study III) effects of rifle carriage were tested in a laboratory using treadmill roller-skiing, whereas the effects of rifle carriage on gear distribution were tested in the field on snow (Study IV). In addition, the effects of supplementary rifle-carriage training on physiological variables and skiing performance were investigated (Study II).